Consideraciones sobre el tratamiento cruento de las fracturas del cuello del fémur - Valls, José (1937)
The author makes reference to the results of the liltle recomended methods of treatment of fractures of the neck of the femur. The writer points out the advantages of the Smith-Petersen's openmethod of operative treatment, believing that the pegging of the neck of the femur by the open-method is an operation apt to give better results, than the closed reduction (bloodless) of Whitman's method; and that inorder to appreciate its true value, it is necessary to await for sometine and to hope for those remote results, which the operated patients yield, with a technique that guarantees a perfect reduction and an accurate placing of the material of prothesis.